Characterizations of novel pesticide-degrading bacterial strains from industrial wastes found in the industrial cities of Pakistan and their biodegradation potential - Asim, Noreen; Hassan, Mahreen; Shafique, Farheen; Ali, Maham; Nayab, Hina; Shafi, Nuzhat; Khawaja, Sundus; Manzoor, Sadaf (PeerJ, 2021)
Background Lack of infrastructure for disposal of effluents in industries leads to severe pollution of natural resources in developing countries. These pollutants accompanied by solid waste are equally hazardous to biological growth. Natural attenuation of these pollutants was evidenced that involved degradation by native microbial communities. The current study encompasses the isolation of pesticide-degrading bacteria from the vicinity of pesticide manufacturing industries. Methods The isolation and identification of biodegrading microbes was done. An enrichment culture technique was used to isolate the selected pesticide-degrading bacteria from industrial waste. Results Around 20 different strains were isolated, among which six isolates showed significant pesticide biodegrading activity. After 16S rRNA analysis, two isolated bacteria were identified as Acinetobacter baumannii (5B) and Acidothiobacillus ferroxidans, and the remaining four were identified as different strains of Pseudomonas aeruginosa (1A, 2B, 3C, 4D). Phylogenetic analysis confirmed their evolution from a common ancestor. All strains showed distinctive degradation ability up to 36 hours. The Pseudomonas aeruginosa strains 1A and 4D showed highest degradation percentage of about 80% for DDT, and P. aeruginosa strain 3C showed highest degradation percentage, i.e., 78% for aldrin whilst in the case of malathion, A. baumannii and A. ferroxidans have shown considerable degradation percentages of 53% and 54%, respectively. Overall, the degradation trend showed that all the selected strains can utilize the given pesticides as sole carbon energy sources even at a concentration of 50 mg/mL. Conclusion This study provided strong evidence for utilizing these strains to remove persistent residual pesticide; thus, it gives potential for soil treatment and restoration.
Keywords: Organo-pesticides; Biodegrading-bacteria; Molecular characteristics; Phylogenetic analysis; 16S rRNA